Methods of protecting buried pipelines and culverts in transportation infrastructure using EPS geofoam. Issue 5 (October 2015) - Bartlett, Steven F.; Lingwall, Bret N.; Vaslestad, Jan
Abstract Expanded polystyrene (EPS) geofoam is an ultra-light geosynthetic often incorporated in transportation infrastructure to reduce horizontal and vertical stresses imposed on buried pipeline and culvert systems. This paper summarizes EPS embankment and cover configurations recently implemented in roadway and railway systems to protect buried conveyances that traverse under or through these transportation systems. These are: (1) light-weight embankments, (2) imperfect trenches, (3) slot-trench cover systems and (4) post and beam cover systems. Also highlighted is research recently performed to develop a slot-trench cover system designed to protect buried, high-strength steel pipelines from potential rupture resulting from vertical permanent ground deformation (e.g., tectonic faulting). Laboratory and full-scale tests and numerical modeling were conducted to develop and implement the concept. The results of the evaluation program show that EPS geofoam blocks can be used as a light-weight, slot-trench cover system in urban roadways to protect buried high-strength steel pipelines threatened by potential rupture resulting from faulting, or other sources of permanent ground deformation.